2010
DOI: 10.1007/s10669-010-9293-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of duckweed growth on water quality in sub-tropical ponds

Abstract: Field experiments on duckweeds, Lemna aequinoctialis, were carried out to determine the effect of plant characteristics on water-quality variables in ponds. In view of their rapid growth rates and ability to cover water surfaces very quickly, such studies are necessary, especially in sub-tropical countries, in order to develop viable management strategies. Morphological parameters like leaf length, leaf width, and root length of individual plants along with cover percent of Lemna were studied in each pond alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…Duckweeds are capable of colonizing open water surfaces in several days on account of their extremely rapid growth rate. 17,30 In the present study, duckweed biomass was estimated to be maintained at about 90 g (dry weight) m −2 (about 1250 g (fresh weight) m −2 ) in floodwater (Fig. 3), which was similar to the biomass of 1600 g (fresh weight) m −2 in wastewater reported previously.…”
Section: Weed Controlsupporting
confidence: 89%
See 1 more Smart Citation
“…Duckweeds are capable of colonizing open water surfaces in several days on account of their extremely rapid growth rate. 17,30 In the present study, duckweed biomass was estimated to be maintained at about 90 g (dry weight) m −2 (about 1250 g (fresh weight) m −2 ) in floodwater (Fig. 3), which was similar to the biomass of 1600 g (fresh weight) m −2 in wastewater reported previously.…”
Section: Weed Controlsupporting
confidence: 89%
“…Formation of the duckweed covering layer was the main factor in suppressing weed growth. Duckweeds are capable of colonizing open water surfaces in several days on account of their extremely rapid growth rate 17, 30 . In the present study, duckweed biomass was estimated to be maintained at about 90 g (dry weight) m −2 (about 1250 g (fresh weight) m −2 ) in floodwater (Fig.…”
Section: Discussionmentioning
confidence: 54%
“…They are probably the best macrophyte to convert nutria-ent to biomass [3,[8][9][10]. Duckweeds systems have been used to remove pollutants from varying qualities of domestic wastewater [3,6,[11][12][13][14], septage [15], and agricultural wastewater such as swine water [13,16]. It has been reported that these plants help in the uptake of heavy metals from polluted waters as well as improve the overall quality of eutrophic water bodies [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Fantail goldfish was successfully reared in this study when the pH range was 7.81 ± 0.39 to 7.89 ± 0.46. The impact of duckweed growth on water quality in sub-tropical pond sediment has been reported to be significant at pH values 6.9 and 9.1 [32]. The pH values in ponds with aquatic plants are generally slightly alkaline in the range of 7-8 [18].…”
Section: In Situ Water Qualitymentioning
confidence: 99%